2012
DOI: 10.2485/jhtb.21.359
|View full text |Cite
|
Sign up to set email alerts
|

Differential Signaling by TGF-^|^beta;1 and BMP-2/-7 During Induction of Osteogenic Differentiation of Human Periodontal Ligament Cells-Involvement of a PI3K/mTOR/p70S6K Mechanism

Abstract: Periodontal ligament (PDL) cells are composed of several different kinds of cells including mesenchymal stem cells (MSC). It is well known that these MSC play an important role in the regeneration of periodontal ligament and alveolar bone. The heterodimeric bone morphogenetic protein (BMP-2/-7) is a very potent BMP. However, BMP and TGF-1 signaling pathways that induce and regulate osteogenesis of HPDL cells are not well understood. It was reported that phosphatidylinositol 3-kinase (PI3K), which is activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The PDL is a connective tissue comprising a heterogeneous cell population, including undifferentiated mesenchymal cells, osteoprogenitors, fibroblasts, and cementoblasts. 19) We previously reported that the phosphatidylinositide 3-kinase (PI3K)/Akt/mTOR/p70S6K pathway plays pivotal roles in the regulation of osteogenic differentiation by transforming growth factor-1 (TGF-1) 20) . We also reported that an experimental model that repeated or highdose administration of TGF-1 inhibited osteoblast differentiation of HPDL cells by decreasing insulin-like growth factor-1 (IGF-1) expression and subsequently downregulating PI3K/Akt signaling 21,22) , but Dex combined with BMP2/7 promotes osteoblast differentiation independently of IGF-1 expression unlike TGF-1 23) .…”
Section: Introductionmentioning
confidence: 99%
“…The PDL is a connective tissue comprising a heterogeneous cell population, including undifferentiated mesenchymal cells, osteoprogenitors, fibroblasts, and cementoblasts. 19) We previously reported that the phosphatidylinositide 3-kinase (PI3K)/Akt/mTOR/p70S6K pathway plays pivotal roles in the regulation of osteogenic differentiation by transforming growth factor-1 (TGF-1) 20) . We also reported that an experimental model that repeated or highdose administration of TGF-1 inhibited osteoblast differentiation of HPDL cells by decreasing insulin-like growth factor-1 (IGF-1) expression and subsequently downregulating PI3K/Akt signaling 21,22) , but Dex combined with BMP2/7 promotes osteoblast differentiation independently of IGF-1 expression unlike TGF-1 23) .…”
Section: Introductionmentioning
confidence: 99%